FRI0552 Why Does Joint Pain "Spread"? Knee Pain Predicts Later Shoulder Pain, Due to Muscle Weakness. Data from the Osteoarthritis Initiative. (9th June 2015) - Laslett, L.L.; Otahal, P.; Hensor, E.M.; Kingsbury, S.R.; Conaghan, P.G.
Abstract : Background: Joint pain is common in older adults; typically multiple joints are involved. Pain in multiple sites is associated with more intense pain in affected joints, poorer physical functioning, and worse quality of life. However, little is known about the pattern of multi-site joint pain development. Objectives: To assess whether number of painful joints increases over time, whether pain in certain joints precedes pain in others, and to assess whether the association is mediated by weakness in a cohort of older adults with painful knee osteoarthritis or at risk of knee osteoarthritis in the NIH Osteoarthritis Initiative (OAI). Methods: Participants were categorised as having no knee pain (neither knee painful at baseline and years 1-3), or persistent pain in one or two knees (pain at baseline and on two or more occasions in the same knee over years 1-3). Number of painful joints (neck, back, shoulders, elbows, wrists, hands, hips, knees, ankles, feet) was calculated at each visit. Changes in the number of joints were assessed using mixed effects Poisson regression. Associations between persistent knee pain and incident shoulder pain at year 4 were assessed using log multinomial modelling, adjusted for age, sex, BMI, and CES-D depression score (baseline, change at 4 years) (models 1-3), other lower limb pain (models 2 & 3) and leg weakness, defined as difficulty standing from a sitting position at baseline (WOMAC function subscale 3) (model 3). Results: Number of painful joints increased yearly, by 2.4% (95% CI -0.5%, 5.5%), 1.6% (-1.4%, 4.5%), 3.5% (0.6%, 6.6%) and 5.2% (2.2%, 8.3%) at years 1-4 compared to baseline. In participants with persistent pain in knees only at baseline, who later developed pain in another single joint (n=70), this did not occur randomly across joint types (p<0.001) with incidence greatest in shoulders (28.5%). Participants reporting weakness, higher depression scores and pain in additional lower limb joints at baseline were more likely to develop shoulder pain at year 4 (all p<0.001). Persistent pain in 1 or 2 knees was associated with increased risk of bilateral shoulder pain at year 4 after adjustment for demographic factors (model 1: Table 1 ). Associations attenuated slightly after further adjustment for lower limb pain (model 2). The association between knee pain and the development of shoulder pain was mediated by leg weakness (model 3), as knee pain was associated with weakness (1 knee: β=1.16; 95% CI 1.08, 1.24; 2 knees: β=1.21; 95% CI 1.11, 1.30) and weakness with incident shoulder pain (1 shoulder: relative risk (RR) 1.21; 95% CI 1.06, 1.36; 2 shoulders: RR 1.46, 95% CI 1.25, 1.71). Conclusions: Spread of joint pain over time is not random, with shoulders the most common painful joint following knees. Associations between persistent knee pain and new shoulder pain is mediated by functional leg muscle weakness; therefore muscle weakness appears key to the spread of joint pain. Disclosure of Interest: None declared